Prevalence of oral mucosal lesions and related risk habits in outpatient dental clinics in Malaysia and Yemen / Raji M.S. Hajeb - Hajeb, Raji M. S. (2010)
The purpose of this study is to determine and compare the prevalence of oral mucosal lesions (OML) and related risk habits and the influence of these habits on oral mucosal lesion prevalence among dental outpatients in Malaysia and Yemen during the period from May to October 2009. A total of 554 and 520 dental outpatients from Malaysia and Yemen with mean ages of 41.9± 17.04 years and 36.6±15.62 years respectively were interviewed and examined. The prevalence of OML namely (oral malignant lesions, potentially malignant disorders and other lesions) in Malaysia was 23.29% while the prevalence of oral mucosal lesions in Yemen was 22.30 %. Among the Malaysian dental outpatients, 19.5 % (n=108) were smokers, 1.8 % (n=10) were betel quid chewers and 4.3 % (n=24) had alcohol drinking habit. In Yemeni dental outpatients, the most frequent habit was qat chewing (40.8 %; n=212), followed by smoking (19%; n=99) and shammah (tobacco quid) chewing (4.4%; n=23). Fifty-five percent (134) of all participants with oral mucosal lesions were found to indulge in risk habit. While the prevalence of OML and smoking habits are similar, statistically significant difference was found in the prevalence of quid chewing between Malaysian and Yemeni dental outpatients. There is a low prevalence of alcohol drinking habit among Malaysians with no such habit among Yemenis; while there is a high prevalence of qat chewing habit among Yemenis but there are no such habits among the Malaysian. There is a higher prevalence of oral mucosal lesions among the dental outpatients who have risk habits as compared to those without habits and this relationship was found to be statistically significant (p < 0.001).